TRAINING VOLUME AND CONCUSSION RISK IN MALE YOUTH ICE HOCKEY PLAYERS: A PRIMARY PREVENTION PERSPECTIVE. Issue 4 (1st February 2017) - Blake, Tracy; MacDonald, Kerry; Palacios-Derflingher, Luz; Emery, Carolyn
Abstract : Background: There is a growing body of evidence illustrating the contribution of training load to musculoskeletal injury risk. There is a gap in the literature, however, regarding the impact of training on concussion risk. Objective: To evaluate the association between sport-specific participation volume and concussion risk in male youth ice hockey players. Design: Cohort study. Setting: Community ice rinks and sport medicine clinics (2011–15 hockey seasons). Patients (or Participants): Male Pee Wee (11–12 years old), Bantam (13–14 years old) and Midget (15–17 years old) ice hockey players were eligible. Players were excluded if they reported unhealed injuries at study entry, had missing/systematically incomplete hockey participation exposure data, or if they sustained a concussion but participation volume could not be estimated from the day of injury. Interventions (or Assessment of Risk Factors): Cumulative hockey participation volume (CPHV) was estimated based on participation exposure data reported by team designate. The association between concussion risk and total 7-day and 28-day CHPV was evaluated using multivariable logistic regression [OR (95%CI)]. Models were adjusted for concussion history and cluster by player (α<0.05). ORs with 95%CI that did not cross one were considered significant. Main Outcome Measurements: Medically diagnosed concussion. Results: Participants who met the inclusion criteria (n=1235/1990) sustained 34 medically diagnosed concussions. Increased concussion risk was associated with hourly increases in 7-day CHPV [OR=1.16 (95%CI: 1.08–1.25), p<0.05] and 28-day CHPV [OR=1.04 (95%CI: 1.01–1.06), p<0.05]. There was no evidence of effect modification or confounding by concussion history. Conclusions: Increased hockey participation volume was associated with increased concussion risk in male youth ice hockey players. This is the first study to explore the association between training volume and concussion risk. Future research utilizing objective volume measurements and training response tools will be critical to the development of primary concussion prevention strategies that optimize the role of training load.